Factors Associated with Mothers’ Knowledge about Sudden Infant Death Syndrome - Anselmo, Mariana Gabriela; Lodi, Jucilene Casati; Milagres, Clarice Santana; Cressoni, Valéria Dulce; Mendes, Karine Laura Cortelazzi; Possobon, Rosana de Fátima (O Mundo da Saúde, 2023)
Sudden Infant Death Syndrome is defined as the death of any infant under one year of age, with a sleeping position, in the prone position, being the most important risk factor. Thus, the massive dissemination of risk factors for this syndrome is fundamental so that mothers, specifically, would know these factors and be able to avoid this accident. Therefore, the objective of this study was to verify the knowledge of mothers about the risk and protective factors for sudden infant death syndrome and its association with socioeconomic and demographic conditions. 502 mothers of children who went for a polio vaccination participated. Socioeconomic and demographic information and mothers’ knowledge of factors associated with the syndrome were collected. A chi-square test was performed to associate the dependent variable (number of mothers’ correct answers) with the independent variables (socioeconomic and demographic data). Analysis of variance (ANOVA) was used for age, income, and level of education and a generalized linear model for social exclusion. Most mothers (72.34%) reported having heard about the syndrome; however, only 51.9% knew how to describe it. There was an association between lower accuracy in the questions (p=0.0001) and never having heard about the syndrome. Mothers who had not heard about it and got fewer questions right lived in neighborhoods with a worse social exclusion index than those who had already heard about it. It is concluded that mothers who had never heard about the syndrome and consequently answered fewer questions correctly, lived in neighborhoods with a worse social exclusion index than those who had already heard about the syndrome. However, among all the factors related to the syndrome, the sleeping position was the one with the highest number of correct answers by the mothers.